CFD analysis of hover performance of rotors at full- and model-scale conditions. (13th June 2016) - Barakos, G.N.; Jimenez Garcia, A.
ABSTRACT: Analysis of the performance of a 1/4.71 model-scale and full-scale Sikorsky S-76 main rotor in hover is presented using the multi-block computational fluid dynamics (CFD) solver of Glasgow University. For the model-scale blade, three different tip shapes were compared for a range of collective pitch and tip Mach numbers. It was found that the anhedral tip provided the highest Figure of Merit. Rigid and elastic full-scale S-76 rotor blades were investigated using a loosely coupled CFD/Computational Structural Dynamics (CSD) method. Results showed that aeroelastic effects were more significant for high thrust cases. Finally, an acoustic study was performed in the tip-path-plane of both rotors, showing good agreement in the thickness and loading noise with the theory. For the anhedral tip of the model-scale blade, a reduction of 5% of the noise level was predicted. The overall good agreement with the theory and experimental data demonstrated the capability of the present CFD method to predict rotor flows accurately.